Azolla microphylla and Pseudomonas aeruginosa for bioremediation of bioethanol wastewater - Khoirul Annisa; SUTARNO SUTARNO; SLAMET SANTOSA (Society for Indonesian Biodiversity, 2021)
Abstract. Annisa K, Sutarno, Santosa S. 2021. Azolla microphylla and Pseudomonas aeruginosa for bioremediation of bioethanol wastewater. Biodiversitas 22: 1799-1805. Bioremediation is the right choice in wastewater treatment since it requires has low cost but works optimally. Azolla microphylla and Pseudomonas aeruginosa are considered to have the ability to optimize waste degradation. The aim of this study was to determine the best treatment for reducing pollutants in bioethanol waste, namely by using A. microphylla and P. aeruginosa. The twelve treatments in this experimental research included variations in the A. microphylla biomass and variations of biomass combinations with the density of the P. aeruginosa. Research method used was completely randomized design with three replications, and all 36 samples were taken on the seventh day. Research data collected were the quality parameters of bioethanol wastewater before and after the treatment. The results showed that TSS, BOD, COD were decreased during seven days of treatment, whereas pH and H2S levels were increased. The combination of 0.2 kg A. microphylla and 1010 cfu/mL P. aeruginosa showed the best result in reducing pollutants. This study showed that A. microphylla and P. aeruginosa could be used to reduce pollutants in bioethanol wastewater. Results of the research are expected to become an alternative solution to the bioethanol wastewater problem.